2021
DOI: 10.1177/11297298211046751
|View full text |Cite
|
Sign up to set email alerts
|

A pig model of tunneled dialysis catheter (TDC) infection and dysfunction: Opportunities for therapeutic innovation

Abstract: Background: Although tunneled dialysis catheters (TDC) are far from ideal, they still represent the main form of vascular access for most patients beginning dialysis. Catheters are easy to place and allow patients instant access to dialysis, but regardless of these benefits, catheters are associated with a high incidence of significant complications like bloodstream infections, central venous stenosis, thrombosis, and dysfunction. In the present study, we aim to describe and characterize a swine model of cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In pigs, a bloodstream infection is denoted by a sustained body temperature of >103.5 °F coupled with either a decrease in appetite or activity. Such infections occur readily in this model of catheter use, with a median time to infection reported as 9 d . Notably, the time to infection was increased from 11.3 ± 8.4 d (control) to 22.7 ± 5.3 d upon using the NO-releasing lock solutions, a 100% relative improvement (Figure C).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In pigs, a bloodstream infection is denoted by a sustained body temperature of >103.5 °F coupled with either a decrease in appetite or activity. Such infections occur readily in this model of catheter use, with a median time to infection reported as 9 d . Notably, the time to infection was increased from 11.3 ± 8.4 d (control) to 22.7 ± 5.3 d upon using the NO-releasing lock solutions, a 100% relative improvement (Figure C).…”
Section: Resultsmentioning
confidence: 86%
“…Catheter placement was performed to mimic placement in human patients . Following placement, blood was flushed in and out of the catheters twice weekly to simulate a dialysis event. , In between events, catheters were locked using either the heparin control or NO-releasing lock solution as would be done during the interdialytic period in patients. The study was maintained for 28 d unless pigs developed a nonresponsive CRBSI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research in a pig model identified cells in the venous neointima that were positive for a-smooth muscle actin, CD68, Ki67, smoothelin, and vimentin. 70 Movement of the catheter with respiration, head movements, changes in position, increased flow and turbulence during maturation of the arteriovenous access, and changes in shear stress lead to deposition of platelets and venous wall remodeling. 71 Meanwhile, trauma to the vessel wall contributes to generation of thrombin, activation of platelets, and expression of P-selectin with an inflammatory response and activation of leukocytes, all of which cause release of myeloperoxidase and development of platelet aggregates, which deposit into thrombi inside the vascular lumen.…”
Section: Catheter Infectionmentioning
confidence: 99%